"Bao wei quan" 保位權, Chapter 20 of the Chunqiu fanlu 春秋繁露: An Annotated Translation*. Issue 1 (2nd January 2016) - Buljan, Ivana
Abstract : This work provides an annotated translation, together with a brief commentary, of the "Bao Wei Quan" chapter, the 20th chapter of the Chunqiu fanlu . The Chunqiu fanlu is an important Chinese Confucian text. It is ascribed to a pivotal Former Han (206 BCE – 9 CE) scholar, an exegete of the Gongyang zhuan 公羊傳, Dong Zhongshu 董仲舒 (ca. 195–115 BCE). This text offered to readers an ideal of rulership that remained highly relevant to the development of the ethical and political discourse of Chinese Confucianism. Despite its importance, the Chunqiu fanlu has only very recently been fully translated into a Western language, 1 and is one of the rare major classical Chinese texts which still lacks a full Japanese translation. Thus, the purpose of this work is to contribute to the ongoing Chunqiu fanlu translation project and to present to the reader some of the form and content of this influential work.